2021
DOI: 10.1016/j.neuroimage.2021.117784
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal network re-organization across learning and development

Abstract: While it is well understood that the brain experiences changes across short-term experience/learning and long-term development, it is unclear how these two mechanisms interact to produce developmental outcomes. Here we test an interactive model of learning and development where certain learning-related changes are constrained by developmental changes in the brain against an alternative development-as-practice model where outcomes are determined primarily by the accumulation of experience regardless of age. Par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…3 ; Table 2 ). In a real data application ( McCormick et al, 2021 ), we observed that an unmodeled effect of repeated practice artificially inflated the effects of age on learning performance (compare estimates in Table 1 , Table 3 ) exactly as these results would suggest.
Fig.
…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…3 ; Table 2 ). In a real data application ( McCormick et al, 2021 ), we observed that an unmodeled effect of repeated practice artificially inflated the effects of age on learning performance (compare estimates in Table 1 , Table 3 ) exactly as these results would suggest.
Fig.
…”
Section: Resultssupporting
confidence: 63%
“…and age-related changes in outcomes of interest is a persistent issue, the utility of the MLMGM generalizes to many modeling contexts. Experience effects are often treated as a nuisance variable (( Ferrer et al, 2004 ; Rabbitt et al, 2001 ) but see ( McCormick et al, 2021 )) that contaminates the developmental effect. As such, MLMGMs can be used to partial out variance associated with repeated assessment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It produces statistical inference maps and probability maps, "which display the likelihood of a given term being used in a study if activation is observed at a particular voxel." More detailed information about the methods used to generate the images is available in the platform's methods paper (Yarkoni et al, 2011) Braams, Raijmakers, Peters, Van Duijvenvoorde, Koolschijn, & Crone, 2016), the results demonstrate (1) that complex learned behaviors involve the integrated and dynamic coordination of distributed brain circuits (Gerraty et al, 2018), and (2) adolescence may be a unique life phase for increased feedback-learning performance, particularly when it interacts with prior skill or experience (McCormick et al, 2021).…”
Section: Reinforcement Learning and Decision-makingmentioning
confidence: 99%